Menumbuhkan Jiwa, Perilaku dan Nilai Kewirausahaan Dalam Meningkatkan Kemandirian Bisnis - Deddy Hendarwan (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
Attitudes and behaviors are the unity of a person's character which is formed by habit everyday. Entrepreneurial behavior is influenced by internal and external factors. These factors are ownership rights (property right, PR), abilities / competencies (competency / ability,), and incentives while external factors include the environment thus Attitudes and behavior can be changed by oneself and / or there are environmental pressures / influences. there is an influence from within themselves and from outside the environment to associate then grow indi attitudes and specific behaviors. It is necessary to anticipate small businesses’ difficulties by conducting an empirical study on the entrepreneurial spirit, entrepreneurial values, and assessment of entrepreneurial behavior that may affect the realization of independence efforts. This study aims to analyze the influence of entrepreneurial spirit and entrepreneurial values on entrepreneurial behavior to create business independence. The findings show that the entrepreneurial spirit has a direct positive influence on entrepreneurial behavior and positive indirect effect on the business independence.